1988
DOI: 10.1007/bf02624192
|View full text |Cite
|
Sign up to set email alerts
|

Production of growth factors related to fibroblast growth factor and platelet-derived growth factor by human embryonal carcinoma cells

Abstract: Previous studies have demonstrated that mouse embryonal carcinoma (EC) cells produce at least two growth factors: one related to platelet-derived growth factor (PDGF) and another related to basic fibroblast growth factor (FGFb). Since human EC cell lines are being used with increased frequency, the current study examined whether human EC cells produce growth factors, in particular those produced by mouse EC cells. In this study, it was determined that the human EC cell line NT2/D1 produces a heat-labile hepari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…The high expression level of NANOG may account for the ability of NT2 cells to grow well in the absence of feeder cells as has been reported for hES cells expressing high levels of NANOG [68]. Furthermore, human EC cells have been reported to produce FGF2 [69], [70]. We have confirmed that NT2 cells express FGF2 as well as EGF mRNA.…”
Section: Discussionsupporting
confidence: 84%
“…The high expression level of NANOG may account for the ability of NT2 cells to grow well in the absence of feeder cells as has been reported for hES cells expressing high levels of NANOG [68]. Furthermore, human EC cells have been reported to produce FGF2 [69], [70]. We have confirmed that NT2 cells express FGF2 as well as EGF mRNA.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have established that EC cells not only produce growth factors such as platelet-derived growth factor (12)(13)(14), insulin-like growth factor (14-16), fibroblast growth factor (13,(17)(18)(19), transforming growth factors a and ß (14) and several incompletely characterized growth factors (17), but they possess also the receptors for growth factors (12,16,20,21). In spite of these many reports about growth factors in EC cells, the production of EGF by teratocarcinoma cells has not been shown until the report of Jing et al (10), which demonstrated the secretion of polypeptides related to EGF in PA-1 cells by means of a bioassay for EGF using the GH26H cell line and Western blot.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-/3 is a potent stimulator of extracellular matrix deposition (reviewed in [48]). In addition the TGF-Bs might co-operate with platelet-derived growth factor (PDGF) produced by human EC cells [56,621 and stimulate the growth of the infiltrating fibroblasts in a progressing teratocarcinoma In addition the TGF-Bs might co-operate with platelet-derived growth factor (PDGF) produced by human EC cells [56,621 and stimulate the growth of the infiltrating fibroblasts in a progressing teratocarcinoma…”
Section: Discussionmentioning
confidence: 99%